The glucocorticoid antagonist mifepristone attenuates sound‐induced long‐term deficits in auditory nerve response and central auditory processing in female rats. Issue 6 (12th January 2018) - Singer, Wibke; Kasini, Kamyar; Manthey, Marie; Eckert, Philipp; Armbruster, Philipp; Vogt, Miriam Annika; Jaumann, Mirko; Dotta, Michela; Yamahara, Kohei; Harasztosi, Csaba; Zimmermann, Ulrike; Knipper, Marlies; et al.
ABSTRACT: Systemic corticosteroids have been the mainstay of treatment for various hearing disorders for more than 30 yr. Accordingly, numerous studies have described glucocorticoids (GCs) and stressors to be protective in the auditory organ against damage associated with a variety of health conditions, including noise exposure. Conversely, stressors are also predictive risk factors for hearing disorders. How both of these contrasting stress actions are linked has remained elusive. Here, we demonstrate that higher corticosterone levels during acoustic trauma in female rats is highly correlated with a decline of auditory fiber responses in high‐frequency cochlear regions, and that hearing thresholds and the outer hair cell functions (distortion products of otoacoustic emissions) are left unaffected. Moreover, when GC receptor (GR) or mineralocorticoid receptor (MR) activation was antagonized by mifepristone or spironolactone, respectively, GR, but not MR, inhibition significantly and permanently attenuated trauma‐induced effects on auditory fiber responses, including inner hair cell ribbon loss and related reductions of early and late auditory brainstem responses. These findings strongly imply that higher corticosterone stress levels profoundly impair auditory nerve processing, which may influence central auditory acuity. These changes are likely GR mediated as they are prevented by mifepristone.—Singer, W., Kasini, K., Manthey, M., Eckert, P., Armbruster, P., Vogt, M. A., Jaumann, M., Dotta, M., Yamahara, K., Harasztosi, C., Zimmermann, U., Knipper, M., Rüttiger, L. The glucocorticoid antagonist mifepristone attenuates sound‐induced long‐term deficits in auditory nerve response and central auditory processing in female rats. FASEB J. 32, 3005–3019 (2018). www.fasebj.org